Shifting evaluations: The impact of status increase on quality evaluations in the movie industry - Chui , Hazel (International Journal of Business Strategy and Social Sciences, 2024)
Contrary to the belief that higher status automatically improves quality evaluations, the purpose of this study was to investigate the effects of status on perceived quality in the movie industry. The research hypothesizes that Academy Award-winning films receive less favorable evaluations post-award and that increased popularity post-award exacerbates this effect compared to their nominated-only counterparts. By analyzing over 47,000 reviews from IMDB, covering both winning and nominated-only movies from 2008 to 2019, the study finds that ratings of award-winning movies significantly decline post-award, while those of nominated-only movies do not experience a similar decline. Despite the decline in ratings, sentiment scores in reviews for award-winning movies do not show a significant drop post-award. Additionally, the study observes that the increase in review volume post-award correlates with lower ratings for winning movies, underscoring the impact of varied audience tastes on evaluations. This phenomenon highlights the divergence in evaluation criteria between experts and the general public. The findings emphasize the complexity of status dynamics and suggest that higher status, as conferred by awards, does not necessarily translate to sustained positive evaluations. This research underscores the need for further exploration into the dynamics of status, popularity, and evaluation, particularly in fields where public perception plays a crucial role. Such insights are valuable for understanding how public recognition and increased visibility can influence the longevity of perceived quality in cultural products.